Gender Performativity in Becky Albertalli’s Simon Vs. the Homo Sapiens Agenda - Hasna Qonitah; Ali Mustofa (Ahmad Dahlan Journal of English Studies, 2022)
This article analyzes Becky Albertalli’s Simon Vs. The Homo Sapiens Agenda (2015) through the lens of gender performativity issues. The performativity experiences of a homosexual person are known to question American society's established beliefs about how individuals should perceive, respond to, and experience gender and sexuality. This research illustrates how gender and sexual identity, as well as cultural constructions of gender and attitudes toward specific sexual orientations, are viewed in the novel's notion of performativity. The article's discussion is framed using Judith Butler's idea of gender performativity.  Through the thematic analysis of the work, it was discovered that societal norms governed gender through a series of performativity. The book's main character, Simon, discovers that it is challenging to express his identity as a homosexual because of the pressure from cultural norms that view people by using sexual orientations other than those of commoners as deviants. However, the main character changes the social perspective so that the idea of having a different sexual orientation is accepted through a series of events.